Pembuatan Portal Website Menggunakan Bootstrap Untuk Media Informasi Kepada Masyarakat di Dinas Komunikasi dan Informatika Kalimantan Timur - Wahyu Hidayat; Muhammad Bagus Indriarto; Denny Rachman; Wawan Joko Pranoto (Universitas Muhammadiyah Manado, 2023)
In the current digital era, the rapid development of information technology is crucial for institutions to utilize existing technology as a means to convey information to the public. This article discusses the creation of a website portal using HTML, CSS, Bootstrap, and JavaScript to serve as an information medium for the East Kalimantan Communication and Information Service. The website aims to provide a comprehensive profile of East Kalimantan, allowing direct access to information related to various regions within the province. The methodology involves analysis, design, development, testing, and maintenance phases. The resulting portal includes features such as main service menus, information services, transparency, government details, state-owned enterprises, mobile services, bureaucratic reform, complaint handling, surveys, and applications, enhancing communication between the government and the public.